Clinical and laboratory determinants of 25-hydroxyvitamin D deficiency during pharmacotherapeutic escalation in heart failure patients - Myrda, Krzysztof; Rozentryt, Piotr; Niedziela, Jacek T.; Ociessa, Aneta; Kasperova, Maria; Hudzik, Bartosz; Nowak, Jolanta U.; Gąsior, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction: The activation of the renin-angiotensin-aldosterone (RAA) system is a main element of the pathophysiology of chronic heart failure (CHF), determining its symptoms and prognosis. Vitamin D is an RAA inhibitor, and its deficiency frequently accompanies CHF. The factors determining the concentration of 25-hydroxyvitamin D [25(OH)D] in CHF are not well understood, although an association has been suggested between the deficiency and the advancement of CHF. Also unknown is the influence of therapeutic escalation using recommended agents on the serum level of 25(OH)D. The aim of this study was to examine the incidence of abnormal 25(OH)D concentrations in CHF patients and to establish the clinical and laboratory determinants of low activity of this metabolite. Material and methods: The retrospective analysis included the data of 412 CHF patients not receiving optimal pharmacological treatment who were initially in NYHA (New York Heart Association) class III or IV. Over the period of 3 months the therapy was escalated until reaching maximum tolerated doses or those recommended by the current guidelines. After optimizing the therapy, the incidence of 25(OH)D deficiency (< 30 ng/ml) and insufficiency (< 20 ng/ml) was established, and clinical and laboratory determinants for these abnormal concentrations were analyzed. Results: Normal serum level, insufficiency, and deficiency of 25(OH)D were observed in, respectively, 41.5%, 26.0% and 32.5% of patients. The NYHA class improved by at least 1 class in 63.6% of patients, remained unchanged in 32.8% of patients, and deteriorated in 3.6% of patients. In multivariables analysis, low availability of natural ultraviolet B (UVB) radiation, loss of body mass during the CHF, higher concentrations of phosphates and albumins, and the presence of diabetes increased the risk of 25(OH)D deficiency, while higher concentrations of uric acid reduced this risk. In patients with a positive response to therapy, the concentration of 25(OH)D was borderline significantly higher (p = 0.055), while insufficiency and deficiency were less frequent (p = 0.02) than in patients without a treatment response, but this pertained only to patients with higher exposure to UVB. These differences were not observed in patients with low UVB exposure. Conclusions : The concentration of 25(OH)D in CHF patients is not associated with the advancement of the disease, but is strongly determined by the potential availability of UVB radiation. A positive response to therapy increases the concentration of 25(OH)D only in the case of high UVB exposure; other determinants of 25(OH)D level include the patient’s metabolic profile and the presence of diabetes.